Enterprise cybersecurity training and awareness programs: Recommendations for success. Issue 4 (2nd October 2019) - He, Wu; Zhang, Zuopeng (Justin)
ABSTRACT: To help employees recognize and change their computing security behavior, organizations need to invest in cybersecurity training and awareness programs to encourage their employees' active engagement in complying with their security policies. However, many organizations' cybersecurity training and awareness programs fail to achieve their goals as employees feel bored with such training programs and lack enthusiasm to participate in them. Highlighting the criticality of the success of cybersecurity training and awareness programs in organizations, this paper identifies best practices and provides actionable insights (relating cyber awareness to employees' personal life, reinforcing security procedures and guidelines, instilling a "relaxed alert" state of employees, and minimizing security fatigue for employees) that will help enterprises develop and implement economical, effective, and engaging cybersecurity training and awareness programs.